Injectable BMP-2 gene-activated scaffold for the repair of cranial bone defect in mice. (12th August 2020) - Sun, Kai; Lin, Hang; Tang, Ying; Xiang, Shiqi; Xue, Jingwen; Yin, Weifeng; Tan, Jian; Peng, Hao; Alexander, Peter G.; Tuan, Rocky S.; Wang, Bing
Abstract: Tissue engineering using adult human mesenchymal stem cells (MSCs) seeded within biomaterial scaffolds has shown the potential to enhance bone healing. Recently, we have developed an injectable, biodegradable methacrylated gelatin-based hydrogel, which was especially effective in producing scaffolds in situ and allowed the delivery of high viable stem cells and gene vehicles. The well-demonstrated benefits of recombinant adeno-associated viral (rAAV) vector, including long-term gene transfer efficiency and relative safety, combination of gene and cell therapies has been developed in both basic and translational research to support future bone tissue regeneration clinical trials. In this study, we have critically assessed the applicability of single-step visible light (VL) photocrosslinking fabrication of gelatin scaffold to deliver rAAV encoding human bone morphogenetic protein-2 ( BMP-2 ) gene to address the need for sustained BMP-2 presence localized within scaffolds for the repair of cranial bone defect in mouse model. In this method, rAAV-BMP-2 and human bone marrow-derived MSCs (hBMSCs) were simultaneously included into gelatin scaffolds during scaffold formation by VL illumination. We demonstrated that the subsequent release of rAAV-BMP-2 constructs from the scaffold matrix, which resulted in efficient in situ expression of BMP-2 gene by hBMSCs seeded within the scaffolds, and thus induced their osteogenic differentiation without the supplement of exogenous BMP-2. The reparative capacity of this novel stem cell-seeded and gene-activated scaffolds was further confirmed in the cranial defect in the severe combined immunodeficiency mice, revealed by imaging, histology, and immunohistochemistry at 6 weeks after cranial defect treatment. : Abstract : Schematic diagram of adeno-associated viral (AAV)-activated visible light photocrosslinking scaffold for cranial bone defect repair in mice. AAV6-human bone morphogenetic protein-2 (BMP-2) vector and human bone marrow-derived mesenchymal stem cells (hBMSCs) were simultaneously incorporated into methacrylated gelatin scaffolds during visible light mediated photocrosslinking. We hypothesize that the released AAV6-BMP-2 construct from the matrix would result in efficient expression of BMP-2 gene from hBMSCs co-seeded within the scaffolds, promoting their osteogenic differentiation, and generating new bone.